Growth of vertically aligned ZnO nanorods arrays by hydrothermal method - Alimanesh, M. (2013)
Well-aligned ZnO nanorod arrays with different average diameters were grown on silicon(100) substrates by hydrothermal method via the precursors of zinc nitrate hexahydrate (Zn(NO3)2.6H2O) and Hexamethylenetetramine (C6H12N4) with equal molar concentration at 0.025 mol/l and 0.05 mol/l. The ZnO nanorods were characterized by X-ray diffraction (XRD) and field emission Scanning electron microscopy (FE-SEM). XRD results indicated that all the ZnO nanorods were preferentially grown along 0001 direction (c-axis). field emission Scanning electron microscopy images showed that the well-faceted hexagonal ZnO nanorods were grown vertically from the silicon(100) substrates. Â© (2013) Trans Tech Publications, Switzerland.